2020
DOI: 10.3390/geosciences10090349
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Intrusion on the Arctic Coast (Svalbard): The Concept of Onshore-Permafrost Wedge

Abstract: Numerous hydrogeological studies on the coastal zone describe the intrusion of sea water inland, salting underground aquifers. The phenomenon is commonly observed in the coasts outside polar areas. However, the impact of sea water has so far not been an object of detailed investigation in a periglacial environment devoid of subsea permafrost. Geophysical measurements at the west coast of the Wedel-Jarlsberg Land in Svalbard indicate that the border between the unfrozen seabed and the frozen ground onshore is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…Without solute exclusion, ice‐saturated permafrost formed under the saltwater boundary, and the saltwater wedge was flushed out. In contrast, with solute exclusion a permafrost wedge formed at the coast, creating initial ice‐saturated permafrost distributions similar to those derived from recent geophysical measurements of such a system (Kasprzak, 2020). Additionally, the saltwater wedge was present and hypersaline conditions (i.e., salinity greater than seawater) were established as observed in high‐latitude marine settings (Harris et al., 2017; Spirina et al., 2017).…”
Section: Methodssupporting
confidence: 56%
“…Without solute exclusion, ice‐saturated permafrost formed under the saltwater boundary, and the saltwater wedge was flushed out. In contrast, with solute exclusion a permafrost wedge formed at the coast, creating initial ice‐saturated permafrost distributions similar to those derived from recent geophysical measurements of such a system (Kasprzak, 2020). Additionally, the saltwater wedge was present and hypersaline conditions (i.e., salinity greater than seawater) were established as observed in high‐latitude marine settings (Harris et al., 2017; Spirina et al., 2017).…”
Section: Methodssupporting
confidence: 56%
“…This situation was visualized using electrical resistivity tomography (ERT) in 2012 on the west coast of Spitsbergen (Kasprzak et al, 2017) and similarly confirmed by geophysical methods also in other locations (Strzelecki et al, 2017;Kasprzak 2020;Kasprzak et al, 2020;Pedrazas et al, 2020). The presence of sea intrusion leads to the formation of a horizontal "permafrost wedge" subjected to changes under influence of air temperature from above and sea water temperature from below, as shown in Figure 5.…”
Section: Permafrost Degradation From the Seamentioning
confidence: 54%
“…Lateral seawater intrusion beneath a thin permafrost base was interpreted by electrical resistivity surveys several decameters inland in Svalbard (Kasprzak et al., 2017), leading to the concept of an onshore‐permafrost wedge (Kasprzak, 2020). Due to seawater intrusion, this concept explains that the thickness of onshore permafrost increases with distance from the coastline.…”
Section: Discussionmentioning
confidence: 99%